Constitutions and religious freedom - Cross, Frank B. (Comparative constitutional law and policy, 2015)
"Many of us take for granted the idea that the right to religious freedom should be protected in a free, democratic polity. This book challenges whether the protection and privilege of religious belief and identity should be prioritized over any other right. By studying the effects of constitutional promises of religious freedom and establishment clauses, Frank B. Cross sets the stage for a set of empirical questions that examine the consequences of such protections. Although the case for broader protection is often made as a theoretical matter, constitutions generally protect freedom of religion. Allowing people full choice in religious beliefs or freedom of conscience is central to their autonomy. Freedom of religion is thus potentially a very valuable aspect of society, at least so long as it respects the freedom of individuals to be irreligious. This book tests these associations and finds that constitutions provide national religious protection, especially when the legal system is more sophisticated"--